Stingless Bees of Mexico The Biology, Management and Conservation of an Ancient Heritage - Quezada-Euán, José Javier G. (Springer International Publishing, 2018)
The stingless bees are the most diverse group of highly social bees and are key species in our planet's tropical and subtropical regions, where they thrive. In Mexico, the management of stingless bees dates back centuries, and they were an essential part of the culture and cosmogony of native peoples like the Maya. In recent decades a vast amount of information has been gathered on stingless bees worldwide. This book summarizes various aspects of the biology and management of stingless bees, with special emphasis on the Mexican species and the traditions behind their cultivation. Much of the information presented here was produced by the author and the team of researchers at the Universidad Autónoma de Yucatán in the course of three decades of working with these insects. Given the breadth of its coverage, the book offers an equally valuable reference guide for academics, students and beekeepers alike.